DESIGN OF AN EYE CLINIC SHIP WITH A HYBRID ELECTRIC ENERGY SOURCE FOR THE NUSA TENGGARA ISLANDS - Triaditya, Charis Febriyan; Nasirudin, Ahmad (Marine & Earth Science and Technology Research Center, DRPM, ITS, 2022)
The World Health Organization reports that cataracts are responsible for up to 77.7% of visually impaired individuals in Southeast Asia, with Indonesia having the largest population of such individuals. Cataracts can grow faster in areas exposed to much exposure to ultraviolet rays, such as the Nusa Tenggara Islands, which cover 3 provinces, namely Bali, West Nusa Tenggara (NTB), and East Nusa Tenggara (NTT). The availability of ophthalmologists in NTB and NTT is still lacking. One ophthalmologist serves 261,969 people in NTB and 871,510 people in NTT. This condition contrasts the target distribution of ophthalmologists according to the 2017-2030 Roadmap for Management of Visual Impairment in Indonesia. The development of the shipping industry has had a negative impact on world carbon dioxide (CO2) emissions. The use of a multi-energy hybrid system is believed to be able to effectively reduce energy consumption and emissions from ships. So, in this study, an innovation in the design of an Eye Clinic Vessel with a hybrid electric energy source was designed using the Spiral Design method. This paper aims to obtain operational patterns, payload, main dimensions, technical calculations, lines plan, general arrangements, safety plans, and 3D models. The ship will serve 14 areas with a ratio of ophthalmologists with a population of more than 1:250,000. Two ships will be built, which will be divided into 2 routes, namely the North Route and the South Route. Each area will be served for one week, so 1 round trip of the Eye Clinic Ship takes around 52 days. This ship has a payload in the form of a minimum deck area for clinical facilities of 228.2 m2 and can accommodate 25 patients with a length overall (Loa) of 38.27 m; Width (B) 10 m; Height (H) 3 m; Draft (T) 1.8 m; and Service Speed (Vs) 13 knots. The ship uses 86 units of solar panels with 120 batteries to store electrical energy. This solar panel can save fuel usage up to 54%.